The Macroeconomic Determinants and the Impact of Sanctions on FDI in Iran - Ghahroudi, Mehdi Rasouli; Chong, Li Choy (Economics and Business, 2020)
We examine the impact of the macroeconomic determinants of foreign direct investment inflows. We also investigate the moderating role of sanctions in FDI inflows into Iran. The results reveal that macro determinants such as infrastructure, exchange rate, inflation rate, investment return, and governance have a long-run effect on FDI inflows in Iran. Our findings also show that GDP growth rate and trade openness have no significant effect on FDI. Our results indicate that sanctions do not have a significant moderating role in the relationship between macroeconomic factors and FDI. Surprisingly, international sanctions have a positive relationship with FDI inflows in Iran. Furthermore, sanctions have a positive impact on the inflation rate and exchange rate in Iran. Finally, our findings show that sanctions have had a significant impact on Iran’s economic growth in recent years due to increasing the severity level of sanctions.